STRATEGY FOR CREATING AN EXPERT SYSTEM BASED ON FUZZY LOGICAL INCLUSION OF MAMDANI TYPE - Viktorivna, Olena (Collection of scientific papers «ΛΌГOΣ», 2023)
It is known that quantitative data (knowledge) can be inaccurate, while there are quantitative estimates of such inaccuracy (confidence interval, significance level, degree of adequacy, etc.). Linguistic knowledge can also be inaccurate. The theory of fuzzy sets is used to account for the inaccuracy of linguistic knowledge. . The use of fuzzy sets allows one to describe fuzzy concepts and knowledge, operate with this knowledge and draw fuzzy conclusions. A prerequisite for the use of fuzzy models is the presence of uncertainty due to the lack of information or the complexity of the system and the availability of qualitative information about the system. The advantages of fuzzy systems include their universality [1].